ANALISIS DAMPAK PENGEMBANGAN DESTINASI PARIWISATA TERHADAP KESEJAHTERAAN MASYARAKAT DI KECAMATAN SINGKAWANG SELATAN KOTA SINGKAWANG - Alan Ilsandi; Putri Tipa Anasi; Ludovicus Manditya Hari Christanto (Universitas Tanjungpura, 2020)
AbstractThis study aims to (1) determine the distribution of tourism provinces in the southern Singkawang sub-district of Singkawang city (2) to determine the impact of the distribution of tourism destinations on the welfare of the community in the southern Singkawang sub-district of Singkawang (3) to determine the priority analysis of the development of tourism destinations in the Singkawang sub-district of Singkawang. This study uses a survey method in the form of direct field observations and interviews with the community and the management. Data analysis techniques use spatial patterns to determine the distribution of tourism destinations, qualitative descriptive techniques to determine the impact on public welfare and analysis techniques use scoring for the priority development of tourism destinations. The results of this study indicate that the distribution of tourism destinations shows a pattern of spread in three villages in the south Singkawang sub-district namely sedau, sijangkung and sagatani. The impact of the spread of tourism destinations shows a positive impact, in the form of increased income and ease in finding work. As for the development priorities found in the village of Mak Jantu Bay fishermen have a high potential to be developed. Keywords: Development Impact, Tourism Destinations, Community Welfare